MATERNAL AGE AT CHILDBIRTH AND AGE OF TYPE 2 DIABETES ONSET IN ADULT OFFSPRING. (16th November 2018) - Davey, A; Torres, R
Abstract: The Centers for Disease Control and prevention estimates that 9.3% of adults in the United States have type 2 diabetes mellitus (T2DM), costing the nation over 245B each year in medical expenditures and reduced productivity. More personalized approaches to prevention that distinguish between individuals with high environmental versus biological risk for T2DM could further reduce public health burden. The present study provides an in-depth examination of the relationship between maternal age and age of T2DM onset in a sample of adults participating in 11 waves of the Health and Retirement Study between 1992 and 2012, as a potential way of disentangling biological and socioeconomic predictors of T2DM. Data for each participant was obtained from the wave in which he or she first reported being diagnosed with type II diabetes or the last wave observed. The final analytic sample consisted of 16, 239 study participants. The main predictor variable utilized in the present study was maternal age, defined as the age of the mother (in years) at the birth of the participant. Cox proportional hazards regression was used to examine the effects of maternal age, demographics and health characteristics on time until type 2 diabetes onset. Advanced maternal age was a significant predictor of age of diabetes onset, operationalized quadratically and as the interaction between maternal age at birth and a binary indicator of whether the mother was ≥30 years at birth.